PENGARUH PEMBERIAN PAKAN KONSENTRAT DAN UREA MOLASES BLOK (UMB) TERHADAP HEMOGLOBIN SAPI POTONG - Jumriah Syam; A.L Tolleng; Umar Umar (Teknosains, 2016)
This study aims to find out how the effect of feed concentrate andthe urea molasses block (UMB) to hemoglobin beef cattle. Riset in SamataFarming Integrated Systems (FIS) Gowa Regency and Lab. IntegratedLivestock Product Technology, Faculty of Science and Technology UINAlauddin Makassar. The method used a randomized block design (RAK) with2 x 6 pattern, (T1; forage 70 + concentrate 30%), (T2; forage 70 + UMB30%), using as 12 heads of bali cattle. Data analysis using t-student. Theresults showed that the concentrate and the urea molasses block (UMB), wasnot significant (P> 0.05) to the hemoglobin value of beef cattle.